INTRODUKSI PROSES PENGOLAHAN PANGAN BERBASIS TANAMAN HORTIKULTURA UNTUK PEMBERDAYAAN MASYARAKAT DESA WUNUT KABUPATEN KLATEN - Danar Praseptiangga; Siswanti Siswanti; Edhi Nurhartadi (SEMAR (Jurnal Ilmu Pengetahuan, Teknologi, dan Seni bagi Masyarakat), 2017)
Wunut Village is located in Tulung Sub-District, Klaten Regency which has the horticultural potential such as tomato and chili. But the huge potential has not been able to lift the economy of the village community. Therefore the community devotion team of Department of Food Science and Technology, Faculty of Agriculture, Sebelas Maret University chose Wunut Village as the target village. The problems faced by farming communities in Wunut Village are (1) production of chili and tomatoes are abundant, but the selling price is relatively low; (2) the large number of poor people; (3) lack of knowledge and community insight about entrepreneurship in the field of food; (4) interest in entrepreneurship is still lacking in society; And (5) the difficulty of marketing the resulting product. The solutions offered by the community devotion team are through training activities and the introduction of tomato processing technology into “torakur”; Training and introduction of production process technology of shredded pepper; Entrepreneurship training and food industry management; Information technology-based marketing training and direct selling strategies. In order to support these activities, aids were also provided to improve the quality of the chakra and the resulting chili pepper. Equipment provided in the form of cabinet dryer, dry mill, and packer sealer. The result of this activity in the form of introduction of tomato processing technology into “torakur”, and processing of chili into shredded chili has been done well, with products that can be accepted by society and have a big prospect to be developed.Keywords:entreprenuership, quality, torakur, shredded chili, Wunut Village